2009
DOI: 10.1080/09540120902814379
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of polyalkylimide gel for the treatment of HIV-associated lipoatrophy

Abstract: The long-term safety and efficacy of products used in the correction of HIV-associated facial lipoatrophy (FLA) are largely unknown. The purpose of this study was to describe the long-term efficacy and safety of polyalkylimide gel (PAIG) in the treatment of HIV-associated FLA. In this open-label, randomized, single-center study, 31 HIV-positive individuals (median age 48 years (interquartile ranges (IQR) 45, 55, 97% male) with FLA were randomized to immediate (week 0 and six) or delayed (week 12 and 18) PAIG i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
11
0
3
Order By: Relevance
“…It can also affect their adherence to medications. There have been several studies that have sought to define the impact of lipodystrophy on HRQOL [148, 150154] as well as studies that have looked at interventions for lipodystrophy [150, 155167]. …”
Section: Co-morbidities/side Effects and The Effect On Hrqolmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also affect their adherence to medications. There have been several studies that have sought to define the impact of lipodystrophy on HRQOL [148, 150154] as well as studies that have looked at interventions for lipodystrophy [150, 155167]. …”
Section: Co-morbidities/side Effects and The Effect On Hrqolmentioning
confidence: 99%
“…The injectables currently in use for lipoatrophy treatment include polyacrylamide gel and hyaluronic acid. The majority of the studies have demonstrated a trend toward improvement in HRQOL scores for these patients, though not all were statistically significant, with improvements seen in the mental health component and social functioning domains especially [155, 160162], though improvement was also seen in the physical domains as well [155]. These studies have used both HIV-specific HRQOL tools such as the MOS-HIV [155, 165] as well as dermatologic and body image-specific tools such as the ABCD or Dermatologic Life Quality Index (DLQI) [158, 159, 163, 164].…”
Section: Co-morbidities/side Effects and The Effect On Hrqolmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of early literature surrounding Bio‐Alcamid suggested good results with minor complication rates 10, 11. Since then it has been used extensively in HIV‐associated facial lipoatrophy with high patient satisfaction rates of up to 95% and improved quality of life using validated surveys 12–15. However, with any synthetic material, the risk of inflammatory reactions, material migration, infection, and difficult removal exists.…”
Section: Introductionmentioning
confidence: 99%
“…Not specified/ not known [142] Prospective study (n = 9), 24 months follow-up # Only mild transient adverse events (e.g., modest inflammatory reaction, edema)…”
Section: Keratoacanthoma-like Reactionmentioning
confidence: 99%